2006
DOI: 10.1177/003335490612100208
|View full text |Cite
|
Sign up to set email alerts
|

Income, Housing, and Fire Injuries: A Census Tract Analysis

Abstract: Given the finding of very high rates of fire injuries in census tracts that are both low income and have older housing, fire prevention units can take preventative measures. Fire protection devices, especially smoke alarms, should be distributed in the neighborhoods most at risk. Multiple occupancy dwellings should have sprinkler systems and fire extinguishers. Laws concerning the maintenance of older rental housing need to be strictly enforced. Vacant houses should be effectively boarded up or renovated for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…In line with previous studies [20,28], this research found a strong relationship between the condition of a dwelling and the rate of fires. When the internal state of a building was viewed as being either clean or tidy, and/or the external condition of a building was in good overall condition, hosts were more likely to have survived than died in accidental residential fires.…”
Section: Ses and Physical Aspects Of A Dwellingsupporting
confidence: 92%
“…In line with previous studies [20,28], this research found a strong relationship between the condition of a dwelling and the rate of fires. When the internal state of a building was viewed as being either clean or tidy, and/or the external condition of a building was in good overall condition, hosts were more likely to have survived than died in accidental residential fires.…”
Section: Ses and Physical Aspects Of A Dwellingsupporting
confidence: 92%
“…Fire prevention strategies (Shai, 2006;Parmer et al, 2006) have played an increasing part in efforts reduce fire incidence in many countries. Crawford (2005) commented that continual reassessment and adjustment of fire prevention activities is necessary in order to attempt to provide a long term solution for reducing fire deaths, injuries and property damage.…”
Section: Fire Preventionmentioning
confidence: 99%
“…As a result of their high "energy burden," low-income households face more utility-related shut-offs and extreme home temperatures, which increase respiratory illness, bronchitis, pneumonia, and even deaths (Hernández, 2008). Low-income households also rely more on antiquated appliances that threaten home safety and increase fire risk (Shai, 2006). Children living in households that experience a high-energy burden are especially at risk for burns from secondary heating sources and carbon monoxide poisoning (Bhattacharya, 2003;Child Health Impact Working Group, 2007;Granade et al, 2009).…”
Section: Introductionmentioning
confidence: 99%